IST Nurse®: development and validity evidence of a mobile application as a support for the clinical management of Sexually Transmitted Infections - Leilane Barbosa de Sousa; Ismael Moreira de Sousa; Edmara Chaves Costa; Ana Paula Fragoso de Freitas; Lydia Vieira Freitas dos Santos; Adriana Gomes Nogueira Ferreira (Universidade de São Paulo, 2024)
Abstract Objective: to develop and evaluate the validity evidence of a mobile application to support nurses in the clinical management of sexually transmitted infections. Method: methodological study conducted in four steps: analysis and definition of requirements; content definition; computational representation with system design; and coding with testing and refinement. In the first steps, nurses with expertise in the subject participated, and in the last, professionals with education in information and communication technology. Data analysis was performed by calculating the Content Validity Index (CVI), considering the minimum agreement value of 0.78. To confirm the viability of the CVI, the binomial test was used through the R software. Variables with p > 0.05 indicated agreement between the judges. Results: the CVI was 0.98 for content, 1.0 for usability and 0.85 for functional performance, showing that the developed application has high validity. Conclusion: it is believed that the IST Nurse® application represents an important technological tool in strengthening evidence-based nursing care. Intervention studies are therefore suggested.